On translation - Sallis, John, 1938- (Studies in Continental thought., 2002)
"Everyone complains about what is lost in translations. This is the first account I have seen of the potentially positive impact of translation, that it represents ... a genuinely new contribution."--Drew A. Hyland In his original philosophical exploration of translation, John Sallis shows that translating is much more than a matter of transposing one language into another. At the very heart of language, translation is operative throughout human thought and experience. Sallis approaches translation from four directions: from the dream of nontranslation, or universal translatability; through a scene of translation staged by Shakespeare, in which the entire range of senses of translation is played out; through the question of the force of words; and from the representation of untranslatability in painting and music. Drawing on Jakobson, Gadamer, Benjamin, and Derrida, Sallis shows how the classical concept of translation has undergone mutation and deconstruction